1997
DOI: 10.1093/treephys/17.7.437
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal photosynthetic responses to light and temperature in white spruce (Picea glauca) seedlings planted under an aspen (Populus tremuloides) canopy and in the open

Abstract: Photosynthetic light and temperature response curves were measured seasonally in seedlings of white spruce (Picea glauca (Moench.) Voss) grown for two years in the understory of aspen (Populus tremuloides Michx.) or in the open in central Alberta. Light-saturated rate of net photosynthesis, the optimum temperature for net photosynthesis, transpiration rate, photochemical efficiency, and stomatal and mesophyll conductances increased from spring to summer and declined thereafter, whereas dark respiration rate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 34 publications
4
67
0
1
Order By: Relevance
“…Studies have shown a relatively flat photosynthetic response to air temperatures between 5 and 15 o C for lodgepole pine, subalpine fir and Engelmann spruce (Huxman et al 2003) and between 10 and 25 o C for Engelmann spruce (DeLucia and Smith 1987). Man and Lieffers (1997b) found a similar photosynthetic insensitivity for white spruce between 5 and 25 o C in the spring and fall, when light is most abundant in understory. During the summer, photosynthesis at saturating irradiance increased with temperature, but there was little difference at lower light levels (e.g., below 150 mol PAR, which would be common in mixedwood understories at moderate broadleaf densities -see Constabel and Lieffers 1996).…”
Section: Influence Of Environmental Factors In Densitydependent Mixedmentioning
confidence: 61%
See 4 more Smart Citations
“…Studies have shown a relatively flat photosynthetic response to air temperatures between 5 and 15 o C for lodgepole pine, subalpine fir and Engelmann spruce (Huxman et al 2003) and between 10 and 25 o C for Engelmann spruce (DeLucia and Smith 1987). Man and Lieffers (1997b) found a similar photosynthetic insensitivity for white spruce between 5 and 25 o C in the spring and fall, when light is most abundant in understory. During the summer, photosynthesis at saturating irradiance increased with temperature, but there was little difference at lower light levels (e.g., below 150 mol PAR, which would be common in mixedwood understories at moderate broadleaf densities -see Constabel and Lieffers 1996).…”
Section: Influence Of Environmental Factors In Densitydependent Mixedmentioning
confidence: 61%
“…Light interception in the overstory increases with broadleaf stem density (or basal area), while light interception in the understory decreases (Comeau 2001, Comeau andHeineman 2003). Consequently, conifer survival, height growth and stemvolume increments in the understory have been shown to be negatively correlated with broadleaf stem density or basal area (Lieffers and Stadt 1994, Man and Lieffers 1997b, Jobidon 2000, Comeau 2001, Lieffers et al 2002. Minimum understory light thresholds for conifer survival may be exceeded in dense broadleaf stands (Pinno et al 2001) with light levels observed as low as 2% full light (Lieffers et al 2002), which can result in high mortality among the most shade-tolerant conifers.…”
Section: Light Limitationsmentioning
confidence: 99%
See 3 more Smart Citations